2016
DOI: 10.1245/s10434-015-5084-0
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Inhibition of Met and EGFR by ME22S, a Novel Met/EGFR Bispecific Monoclonal Antibody, Suppresses the Proliferation and Invasion of Laryngeal Cancer

Abstract: Taken together, our findings suggest that the dual inhibition of EGFR and Met through ME22S largely suppresses the invasion and growth of laryngeal carcinoma both in vitro and in vivo, hence, can be a practical approach as a novel therapeutic strategy for the treatment of laryngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…Analogous data were acquired in 3D conditions, where cells invaded through the layer of the Matrigel. Similarly, Lee and coworkers showed that ME22S (a novel EGFR/MET bispecific antibody) significantly inhibited HGF‐stimulated migration and invasion of laryngeal carcinoma cells . Moreover, it was shown that down‐regulation of EGFR caused by MiR‐615 and MiR‐7, led to decreased migration, and invasion of human glioblastoma and ovarian cancer cells, respectively .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Analogous data were acquired in 3D conditions, where cells invaded through the layer of the Matrigel. Similarly, Lee and coworkers showed that ME22S (a novel EGFR/MET bispecific antibody) significantly inhibited HGF‐stimulated migration and invasion of laryngeal carcinoma cells . Moreover, it was shown that down‐regulation of EGFR caused by MiR‐615 and MiR‐7, led to decreased migration, and invasion of human glioblastoma and ovarian cancer cells, respectively .…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Lee and coworkers showed that ME22S (a novel EGFR/MET bispecific antibody) significantly inhibited HGF-stimulated migration and invasion of laryngeal carcinoma cells. 35 Moreover, it was shown that down-regulation of EGFR caused by MiR-615 and MiR-7, led to decreased migration, and invasion of human glioblastoma and ovarian cancer cells, respectively. 36,37 Analogous effect was observed following MET silencing or its down-regulation in many cancers like ovarian cancer, breast cancer, hepatocellular cancer or gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of protein will give a reference for protein drugs in the treatment of human cancer in library and clinical practice. 31,32 In addition, hTERTR-FAM96A significantly promoted CTL responses and IFN-γ release by inducing tumor cells apoptosis in murine HCC models. Among many apoptosis-related molecules involving tumor cells apoptosis, we focused on Bcl-2, Brg-1, C-myc, Apo-1, Apaf-1, and Bax in hepatic carcinoma cells.…”
Section: Discussionmentioning
confidence: 96%
“…In metastatic colorectal cancer, amplification and overexpression of MET is a key contributing factor to resistance to anti-EGFR therapies (Misale et al, 2014; Takahashi et al, 2016). Furthermore, dual inhibition of MET and EGFR by “biseptic” antibodies, or combined inhibitors, demonstrated effective inhibition of tumor growth in vitro and in vivo (Castoldi et al, 2013; Lee et al, 2016a; Xu et al, 2011), in accord with our findings in GC cluster B. Recently, another dual inhibition of MET and EGFR in GC cells has emerged, based on inhibition of sphingosine 1-phosphate (S1P), a G protein-coupled receptor ligand (Shida et al, 2004).…”
Section: Discussionmentioning
confidence: 99%